PERANCANGAN SISTEM E-VOTING DENGAN MENERAPKAN QR-CODE SEBAGAI SISTEM KEAMANAN MENGGUNAKAN VB.NET UNTUK PEMILIHAN KEPALA DESA - Riyan Ramdhan Nuriyana (PROCEEDING STIMA)
The development of information technology today has brought great changes to humans, including ways to implement voting. The use of computer technology in the implementation of voting is known as electronic voting (e-voting). Sidamukti village is a village located in Majalengka district of course during this process of electing the village head in the sphere of Sidamukti village is still implemented conventionally. Therefore the utilization of information and communication technology raises the idea to make an electronic voting system or commonly called E-Voting based desktop using VB.Net with QR-Code security system. the method used in this study is extreme programming which is divided into several phases. In designing a security system using QR-Code as a voter login authentication on voting apps.